2000
DOI: 10.1034/j.1600-0463.2000.d01-101.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis seropositivity is associated both with stillbirth and preterm delivery

Abstract: The cause of stillbirth and preterm delivery is often unknown. We studied the prevalence of Chlamydia trachomatis antibodies in mothers with stillbirth and preterm labor. Serum specimens from 72 mothers with stillbirth after the 21st gestational week, and from 48 mothers with preterm delivery between gestational weeks 23 and 29, both from the greater Helsinki area, and cord blood from 96 consecutive liveborn deliveries at the Department of Obstetrics and Gynecology, the University of Helsinki, were studied for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…Pregnant women could be a specific target group for C. trachomatis screening. Antenatal screening, as recommended by the Centers for Disease Control and Prevention (3), may be beneficial for decreasing morbidity among women themselves but also to prevent vertical (infant) and horizontal (partner) transmission (2,6,8,9,24). Screening of pregnant women usually yields prevalences similar to those obtained with nonpregnant women.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Pregnant women could be a specific target group for C. trachomatis screening. Antenatal screening, as recommended by the Centers for Disease Control and Prevention (3), may be beneficial for decreasing morbidity among women themselves but also to prevent vertical (infant) and horizontal (partner) transmission (2,6,8,9,24). Screening of pregnant women usually yields prevalences similar to those obtained with nonpregnant women.…”
Section: Discussionmentioning
confidence: 92%
“…Asymptomatic carriers are of substantial importance in the transmission of C. trachomatis infection within a community. Asymptomatic chlamydial infection in pregnant women imposes an additional risk for acute and chronic consequences for the women themselves and their (unborn) offspring (2,6,8,9,16). In The Netherlands, C. trachomatis causes most sexually transmitted infections, with approximately 60,000 new cases estimated for a total population of 16 million in the year 2000.…”
mentioning
confidence: 99%
“…25 It has also been found that serum IgM antibodies, but not IgG antibodies, are associated with preterm delivery, suggesting that acute infection may play a role. 26 We examined the appearance of C. trachomatis IgG antibodies retrospectively as a marker of past infection. However, in the case of preterm delivery, these antibodies may appear later.…”
Section: Discussionmentioning
confidence: 99%
“…Stillbirth, preterm delivery or perinatal death (Dong et al, 1988;Witkin et al, 1992;Fejgin et al, 1997;Gencay et al, 1997Gencay et al, , 2000Ren et al, 1997;Rastogi et al, 1999) as well as neonatal conjunctivitis or pneumonia (Sandstrom et al, 1984;Mardh, 2002) have been reported. Thorp et al (1989) have found that chlamydiae pass through fetal membranes and thus cause pneumonia.…”
Section: Discussionmentioning
confidence: 99%